Associates and integrated producers: the hybrid face of the cooperatives enterprise In the field - Diane Belusso (Revista Raega: O Espaço Geográfico em Análise, 2007)
In this work, it is discussed the hybrid and contradictory featureof a cooperative enterprise. Aspects like the parallel relationbetween “free” and “integrated” producers, the participation ofits associates in the General meetings, among others will beboarded. It checks contracts kept between the cooperative andthe producers of chicken, the rights and duties of both parts andthe levels of dependence or independence between them.